Characteristics of Nutrition Intake in Diabetic Ulcer Patients at Hospital dr. Slamet Garut - Zahara Farhan; Rudi Alfiansyah; Devi Ratnasari; Eti Suliyawati (Jurnal Penelitian Pendidikan IPA, 2023)
Diabetes mellitus can lead to the development of ulcers on the extremities, which are typically caused by peripheral nerve disorders, infections, and blood flow disorders. Managing diabetes requires adhering to proper nutritional intake, including the frequency and duration of meals, as well as the types of foods consumed. In this study, we aimed to examine the nutritional intake characteristics of outpatients with diabetic ulcers at Dr. Slamet Garut, including their eating frequency, meal duration, and food choices. We used a quantitative descriptive research design and selected a sample of 49 diabetic ulcer patients through purposive sampling. Data was collected using a validated and reliable questionnaire. The results of our study indicated that the majority of patients (57.1%) did not eat frequently, had short meal durations (51.0%), and consumed low-calorie foods (61.2%). Diet planning is a major component of success in treating diabetic ulcers. The accuracy and regularity of the patient in setting the amount, type and schedule of meals aims to control glucose levels so that blood flow to the ulcer area becomes smooth and the ulcer healing process will run well. Overall, nutritional intake in patients with diabetic ulcers is largely inadequate during the wound healing process.